Flexural Behavior of Reinforced Concrete Beams Strengthened with Externally Bonded Hybrid Systems - Mohammed, Abubakr Ahmed Abdelall (2017)
A Master of Science thesis in Civil Engineering by Abubakr Ahmed Abdelall Mohammed entitled, “Flexural Behavior of Reinforced Concrete Beams Strengthened with Externally Bonded Hybrid Systems”, submitted in December 2017. Thesis advisor is Dr. Jamal Abdalla and thesis co-advisor is Dr. Rami Hawileh. Soft and hard copy available.